Role of IL-6/RORC/IL-22 axis in driving Th17 pathway mediated immunopathogenesis of schizophrenia. (November 2018) - Subbanna, Manjula; Shivakumar, Venkataram; Talukdar, Pinku Mani; Narayanaswamy, Janardhanan C.; Venugopal, Deepthi; Berk, Michael; Varambally, Shivarama; Venkatasubramanian, Ganesan; Debnath, Monojit
Highlights: Altered expression of transcription factor of Th17 cells could influence schizophrenia. Inducer (IL-6) and effector (IL-22) cytokines of Th17 cells could mediate inflammation in schizophrenia. The components of Th17 pathway can modulate schizophrenia psychopathology. Abstract: The immuno-inflammatory origin of schizophrenia in a subset of patients is viewed as a key element of an overarching etiological construct. Despite substantial research, the immune components exerting major effect are yet to be fully clarified. Disrupted T cell networks have consistently been linked to the pathogenesis of schizophrenia. Amongst the Th cell subsets, the Th17 cells have emerged as a paradigmatic lineage with significant functional implications in a vast number of immune mediated diseases including brain disorders such as schizophrenia. The present study was aimed at examining the functional role of the Th17 pathway in schizophrenia. To address this, genotyping of IL17A (rs2275913; G197A) Single Nucleotide Polymorphism was carried out by the PCR-RFLP method in 221 schizophrenia patients and 223 healthy control subjects. Gene expression of two transcription factors STAT3 and RORC was quantified in a subset of drug naïve schizophrenia patients (n = 56) and healthy controls (n = 52) by TaqMan assay. The plasma levels of fifteen cytokines belonging to Th17 pathway were estimated in a subset of drug naïve schizophrenia patients (n = 61) and healthy controls (n = 50) by using Bio-Plex Pro Human Th17 cytokine assays. The AA genotype was associated with higher total score of bizarre behaviour and apathy in female schizophrenia patients. A high gene expression level of RORC was observed in drug naïve schizophrenia patients. In addition, significantly elevated plasma levels of IL-6 and IL-22, and reduced levels of IL-1β and IL-17F were noted in schizophrenia patients. Taken together, these findings indicate a dysregulated Th17 pathway in schizophrenia patients.